Improvements in the thermal conditioning of high Andean homes in the Puno region - Linares Zaferson, Víctor Eduardo (2022)
During the frost periods in Puno, as in other highlands regions, the most vulnerable population are children and the elderly. They suffer respiratory illnesses and death due to inadequate thermal conditioning in their homes. The objective of the research is to evaluate the thermal behavior of an "improved" housing prototype built in the Santa Rosa district (Puno) at an altitude of 3800 meters. This research propose alternatives for the improvement of thermal conditioning in the manufacture of repetitive modules. For this, it was necessary to characterize the house and continuously monitor the interior and exterior temperatures of two sample houses. The measurement was at an hour interval and during cold days, using DataLogger equipment. The evaluation of these results determined that homes lose heat due to conduction of wall, ceiling, door and window. Also, the heat is lost due to the inadequate home’s orientation in sunlight and ventilation. Alternative solutions were proposed for the thermal conditioning of the "improved" house with respect to the problems encountered. It was observed that the largest area of the envelope made up of adobe walls that represents 60% of the total enclosure, and that despite the fact that this material has a low conductivity coefficient presents 77% of heat losses due to lack of a suitable coating. Through these modifications in the envelope of the improved house, it has been possible to increase the interior temperature by 1.87 ºC during the hours of coldest temperatures and to maintain an average interior temperature of 14 ° C.